Developing Mobile Learning Media on Human Bone Skeleton Material for Grade 5 Elementary School Students - Nofiyanti, Maya; Prayogo, Muhammad Suwignyo (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
Research on the development of application products as learning media for elementary school students as learning media to increase the spirit of learning. This study aims to test the effectiveness of validity and evaluate applications as learning media. This research uses a development method with the ADDIE model, and the results of the observations show that some students experience problems when learning about the human skeleton. This study developed an application that contains material, questions, and scores at the design stage using Kilonotes and Smart Apps Creator. The results of the application media validity test obtained a score of 95% from media experts, assessing aspects of application display design, fonts, images, and practicality. The assessment given by the material expert was 90% based on the aspects of the material, questions, and practicality of learning. Assessment from students regarding application media as learning support is very helpful because the practical application is easy to use when learning outside and at school. Statistical tests show significant results; the value obtained is, on average, high. The results of data analysis of student responses to the media using the N-Gain Test formula show a positive start with a score of 96% of 30 students. It can be concluded that the use of the application as a learning media on grade 5 human skeleton material shows that this application is valid and feasible for use by students.